الفعالية العلاجية لبرنامج ABVD وسلامته عند مرضى الذروة العمرية الأولى في داء هودجكين - عبد الرحمن نافع محمد (Latakia University Journal -Medical Sciences Series, 2019)
في هذه الدراسة طُبق برنامج ABVD على 33 مريض من أعمار الذروة الأولى تراوحت أعمارهم بين 16-36 سنة من مراجعي مشفى الأسد الجامعي والوحدات المهنية التابعة لها. خضع المرضى لمراقبة سريرية ومخبرية وشعاعية، ودرست اختلاطات العلاج ولاسيما تعداد النطاف (قبل وبعد المعالجة). حصلنا على هوادة كاملة عند 100% من مرضى الدرجة II و%84.6 من مرضى الدرجة III و80% من مرضى الدرجة IV للمرض. أما بقيا سنتين من دون نكس فكانت عند 93.3% من مرضى الدرجة الثانية و76.9% من الدرجة الثالثة و60% من مرض الدرجة الرابعة مع اختلاطات عامة غير خطيرة، أما التأثير في الحيوانات المنوية فكان مؤقتاً, ولم يحدث غياب نطاف نهائي عند أي من المرضى. ABVD program was applied in this study on 33 patients with Hodgkin’s disease aged 16-36 years, in Al-Assad University Hospital and its professional units. The patients under-went clinical, laboratory and scan observations. Drug complications were studied, with sperm counts pre and post treatment. We obtained a complete remission in 100% of patients with St. II, in 84.6% with St. III, and in 80% with St. IV patients. Two years follow-up without relapse was seen in 93.3% of the St. II, and in 76.9% of the St. III, and in 60% of the St. IV patients with no serious general complications of the treatment. The effect on sperms was temporary and there was no Azospermia in any patient.